Application of bovine bone meal and oyster shell meal to heavy metals polluted soil: Vegetable safety and bacterial community. (February 2023) - Zheng, Xiongkai; Zhang, Bowen; Lai, Weibin; Wang, Mengting; Tao, Xueqin; Zou, Mengyao; Zhou, Jiangmin; Lu, Guining
Abstract: The development of efficient, environmentally friendly soil amendments is necessary in order to minimize the risk of metal contaminants (Cd, Pb, Cu, and Zn) to the soil ecosystem. As soil amendments, bovine bone meal (BM) and oyster shell meal (OS) reduced the mobility and bioavailability of metals primarily by increasing soil pH. Soil geochemical properties (pH, EC, CEC, Ca, P, and K) after amendment supplementation were more likely to affect metal migration than enzyme activity. Furthermore, BM and OS were found to suppress the Cd and Pb uptake by water spinach, keeping them below international standards for safe utilization. The protein and sugar content and peroxidase (POD) activity showed a significant negative correlation with the amount of metal in water spinach, whereas superoxide dismutase (SOD), ascorbate peroxidase (APX) activities and malondialdehyde (MDA) content exhibited a positive correlation with metal content in water spinach. We also found that BM and OS had less perturbation to phylum-level and genus-level bacterial composition during the remediation of heavy metals contaminated soil. Based on the above, we assume that BM and OS are eco-friendly soil amendments, which could improve soil nutrients contents, stabilize heavy metals and regulate bacterial community structure. Our research contributes to resource utilization of waste and holds promise for widespread application in current agricultural systems. Graphical abstract: Image 1 Highlights: BM and OS reduced the bioavailability of Cd, Pb, Cu, and Zn in soil. BM and OS inhibited the uptake of Cd, Pb, Cu, and Zn by water spinach. BM and OS reduced the abundance of metal-tolerant bacteria in soil. Major geochemical factors altering the bacterial community were identified.